CO2 and temperature variations during peak tourist season in Lepe jame (Postojna Cave, Slovenia) - Perne, Matija (Acta carsologica, 2025)
We present and analyze measurements of CO2 concentration and air temperature taken during the peak tourist season of 2017 in Lepe Jame, a poorly ventilated passage within Postojnska Jama, Slovenia. During the study, the passage was visited by between 5500 and 6500 visitors per day. Both parameters show pronounced diurnal fluctuations, primarily driven by visitor activity. As part of our campaign, we tested and confirmed the effectiveness of enhanced ventilation—achieved by opening the artificial tunnel connecting Postojnska Jama to Črna Jama—in preventing excessively high CO2 concentrations. The measure is, however, questionable, as it affects the microclimate in Črna Jama. Although CO2 concentration and temperature are correlated, notable differences emerge in the shapes of their respective rise and recession curves. Temperature increases more rapidly with the arrival of visitors, while it decreases more slowly after visiting hours compared to CO2. This lag is attributed to thermal storage: heat from visitors is absorbed by the cave walls during the day and gradually released into the cave during the night.
Keywords: carbon dioxide; cave climate; cave monitoring; jamska mikroklima; karst (geology); kras (geologija); monitoring jam; ogljikov dioksid; show caves; turistične jame